2022
DOI: 10.1111/cod.14020
|View full text |Cite
|
Sign up to set email alerts
|

Patients' perspectives on quality of care for chronic hand eczema: A qualitative study

Abstract: Background Hand eczema (HE) has a significant impact on patients’ quality of life and work‐related activities. However, little is known about the patients' perspectives on quality of care for HE. Objectives To evaluate the patient perspective of the HE care process in a tertiary referral center. Methods Qualitative, semi‐structured focus groups were carried out, recorded, transcribed, and analysed using an inductive‐deductive thematic approach. Results Fifteen patients participated in four focus groups. Time a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
21
0
12

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 8 publications
(38 citation statements)
references
References 38 publications
5
21
0
12
Order By: Relevance
“…Like previously interviewed patients with occupational skin disease, 8 our participants might be forced to face retraining or unemployment and could therefore be worried about their occupational future. We confirmed that CHE impaired emotional well‐being 2,5,6,8–10,20 and daily activities 5,6,9,11 . In contrast to Danish CHE patients, 9 CHEPEP participants did not describe themselves as indolent due to these restrictions.…”
Section: Discussionsupporting
confidence: 75%
See 3 more Smart Citations
“…Like previously interviewed patients with occupational skin disease, 8 our participants might be forced to face retraining or unemployment and could therefore be worried about their occupational future. We confirmed that CHE impaired emotional well‐being 2,5,6,8–10,20 and daily activities 5,6,9,11 . In contrast to Danish CHE patients, 9 CHEPEP participants did not describe themselves as indolent due to these restrictions.…”
Section: Discussionsupporting
confidence: 75%
“…As previously reported, our participants were concerned about the safety of treatments, 6 in particular corticosteroids, 6,11 and relapses after treatment. 6,11 However, they were open to treatment recommendations.…”
Section: Therapymentioning
confidence: 98%
See 2 more Smart Citations
“…Figure 1 shows the PRISMA flow diagram of the selection criteria. A total of 1398 studies were screened, and 249 studies (17.8%) were ultimately included in the database …”
Section: Resultsmentioning
confidence: 99%